Shariah governance disclosure by Islamic banks in Malaysia - Fatihah, Abd Rahaman (2015)
Shariah governance is the utmost important division of Islamic banks to differentiate with its conventional counterpart. Although Islamic banks had been in the Malaysian banking industry for more than three decades, it is still at the stage towards comprehensive and proper framework. Besides, Islamic banks have the responsibility to ensure Shariah compliance in its overall operation. Non-compliance element will damage the confidence of the stakeholders and the perception on the purity of Islamic banking system. Thus, this study intends to scrutinize the scope of latest regulations on Shariah governance in Islamic banks, then comparing it with the international standard and to analyze its practice in compliance with the stipulated guidelines. These purposes are achieved by using qualitative method of research by applying doctrinal and legal research where the latest annual report and few regulations are referred. Besides, the descriptive and comparative study was also adopted for deep understanding. All data was taken from the Islamic banks listed under BNM and analysed it using content analysis. The practice of Shariah governance was examined by using Shariah governance disclosure ratio on the items in the SC report based on referred regulations. This study found that Malaysian regulations on Shariah governance of Islamic banking are more comprehensive rather than the international standard. However, only few Islamic banks comply with the guidelines, whilst the transition period for the compliance is almost end. Thus, it is recommended for the authorities to ensure Shariah governance disclosure been fully complied by the related Islamic banks. As the result, a proper and comprehensive Shariah governance in Islamic banks in Malaysia could be achieved.